Crystal-Phase- and B-Content-Dependent Electrochemical Behavior of Pd─B Nanocrystals toward Oxygen Reduction Reaction - Wahidah, Hafidatul; Chun, Hee Joon; Kim, Woo Hyeok; Kim, Tae Wu; Kim, Seok Ki; Hong, Jong Wook (Small, 2024)
The manipulation of crystal phases in metal–nonmetal interstitial alloy nanostructures has attracted considerable attention due to the formation of unique electronic structures and surface atomic arrangements, resulting in unprecedented catalytic performances. However, achieving simultaneous control over crystal phase and nonmetal elements in metal–nonmetal interstitial alloy nanostructures has remained a formidable challenge. Here, a novel synthesis approach is presented for Pd─B interstitial alloy nanocrystals (NCs) that allows investigation of the crystal-phase- and B-content-dependent catalytic performance. Through comparison of the oxygen reduction reaction (ORR) properties of Pd─BX interstitial alloy NCs with different crystal phases and B contents, achieved by precise control of reaction temperature and time, the influences of crystal phase and B contents in the Pd─BX interstitial alloy NCs on ORR are precisely investigated. The hexagonal closed packed (hcp) PdB0.5 NCs exhibit superior catalytic activity, with mass activities reaching 2.58 A mg−1, surpassing Pd/C by 10.3 times, attributed to synergistic effects by the hcp crystal phase and relatively high B contents. This study not only provides a novel approach to fabricate interstitial alloy nanostructures with unconventional crystal phases and finely controlled nonmetal elements but also elucidates the importance of crystal phase and nonmetal element content in optimizing electrocatalytic efficiency.
Keywords: Alloy nanocrystals; Catalytic performance; Content dependent; Crystal phasis; Electrochemical behaviors; Interstitial alloys; Non-metallic; Nonmetallic doping; Oxygen reduction reaction; PdB nanocrystal; nonmetallic doping; oxygen reduction reaction; PdB nanocrystal